2006
DOI: 10.2332/allergolint.55.287
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Open-Label Comparative Study of Montelukast versus Theophylline Added to Inhaled Corticosteroid in Asthmatic Children

Abstract: The results indicate that montelukast added to low-dose ICS is an effective and safe option for the treatment of asthma in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The observed safety and tolerability results are consistent with the safety profile of montelukast previously reported in asthma childhood [2,13,14,22,24-26,37-39]. …”
Section: Discussionsupporting
confidence: 90%
“…The observed safety and tolerability results are consistent with the safety profile of montelukast previously reported in asthma childhood [2,13,14,22,24-26,37-39]. …”
Section: Discussionsupporting
confidence: 90%
“…46 Less serious side effects of montelukast occur uncommonly, but may include pharyngitis, dizziness, nausea, headache, diarrhea, fever, abdominal pain and rash. 33,36,[41][42][43][44] The incidence of adverse events associated with montelukast is comparable to those of other standard therapies for asthma in childhood and in some studies montelukast was equivalent to placebo. 40 Although FDA approval for montelukast has been obtained for children $2 years of age, safety data to date suggest that this agent may also be used for younger patients between the ages of 6 months and 2 years.…”
Section: Safetymentioning
confidence: 68%
“…33,[36][37][38][39][40][41][42][43][44][45] Serious adverse events, such as worsening asthma, appear to be rare 46 and all reported patients with drug overdoses recovered without sequelae. 46 Less serious side effects of montelukast occur uncommonly, but may include pharyngitis, dizziness, nausea, headache, diarrhea, fever, abdominal pain and rash.…”
Section: Safetymentioning
confidence: 99%
“…70, 71 One small trial showed that the addition of theophylline to inhaled corticosteroids resulted in improvement in peak expiratory flow, but did not improve FEV1 or bronchial reactivity. 72 Given the lack of substantial supporting evidence, potential toxicity, and need for frequent monitoring, theophylline is not part of first-line therapy for children with asthma and is not recommended for children under 5.…”
Section: Alternatives To Inhaled Corticosteroidsmentioning
confidence: 99%